External Validation of Risk Scores for Clinically Significant Hypocalcemia in Patients Underwent Total Thyroidectomy, A Retrospective Study - Krittayot Patchanee, M.D.; Nilnetre Mahathanaruk, M.D.; Phurich Praneetvatakul, M.D. (Thai Journal of Otolaryngology Head and Neck Surgery, 2023)
Abstract Introduction Hypocalcemia is among the most common post-operative total thyroidectomy complications. There are established risk factors predicting risk of hypocalcemia in patients underwent total thyroidectomy. However, there is no single factor with high predictive power for post-operative hypocalcemia or factors which predict hypocalcemia before surgery. There are several risk scores published but not widely acceptable and there is no study externally validate those scores. Risk scores by Pradeep¹ and Papanastasiou (CaReBe’S TiP Score)² were externally validated using database of Faculty of Medicine Ramathibodi Hospital. Objective To externally validate risk scores by Pradeep¹ and Papanastasiou² and find their predictive powers Study design A retrospective database of patients underwent total thyroidectomy during 2017-2021 were obtained. Sensitivity, specificity, odds ratio were calculated from 2 risk scores. Results: CaReBe’s Tip score from 3 and above has sensitivity and specificity 81.21% and 63.79%. For the score 4 and above, sensitivity and specificity is 18.18 and 93.10. Area under ROC is 0.754. Post- operative PTH level is the only factor that associated with 24-hr post-operative hypocalcemia and clinically significant hypocalcemia for both scores. Due to limitation of data, predictive power of Pradeep’s score cannot be calculated. Number of preserved parathyroid gland of less than and equal to 2 glands significantly predicts permanent hypoparathyroidism. Conclusion: Post-operative PTH level below 14.9 pg/mL is a strong predictor for post-operative hypocalcemia. Keywords: total thyroidectomy, hypocalcemia, risk score